Correlation between CD4 count and glomerular filtration rate or urine protein:creatinine ratio in human immunodeficiency virus-infected children - Aliyannissa, Almira (Kidney Res Clin Pract, 2020)
BACKGROUND: Studies on kidney complications in human immunodeficiency virus (HIV)-infected children are lacking. CD4 T lymphocytes are an important immune functions regulator and used as a basis for initiating antiretroviral therapy (ART) and monitoring disease progression. This study aims to determine the correlation between CD4 and estimated glomerular filtration rate (eGFR) or urine protein:creatinine ratio (uPCR) as markers of kidney complications. METHODS: This cross sectional study was conducted on HIV-infected children aged 5 to 18 years who visited the Teratai HIV Clinic at Hasan Sadikin Hospital for monthly monitoring in June 2019. CD4 count, eGFR based on the Schwartz formula, and uPCR were obtained. Correlation analysis was performed with the Pearson test. RESULTS: Subjects were 42 HIV-infected children, consisting of 23 males (54.8%) and 19 females (45.2%). Most children (65.0%) were in an advanced clinical stage and had been diagnosed with HIV for an average of 8 ± 3 years. All subjects had received ART, and six received tenofovir. Compliance to medications were good, and most subjects (79.0%) had normal nutritional status and CD4 count. All subjects had eGFR > 90 mL/min/1.73 m(2), of which 21 (50.0%) were above normal value. Proteinuria was found in 12 patients (28.6%), and it was not significantly associated with clinical stages of HIV infection. CD4 count was correlated positively with eGFR (r = 0.473, P = 0.001) and negatively with uPCR (r = -0.284, P = 0.034). CONCLUSION: The degree of immunodeficiency appears to correlate with severity of renal injury. Screening at diagnosis and periodic monitoring of kidney functions are crucial in all childhood HIV patients.